(untitled) (Academia Science Repository, 2023)
This article discusses the current use of chemicals in forensics. The relevance of works on this topic is noted in many literatures. The work provides a far from complete list. Tasks facing the experts, which are solved with using instrumental analytical methods. Creation of new analytical techniques on the basis of more advanced methods, techniques and equipment will determine the further development forensic examination.